Challenges for German Development Cooperation in the Run-up to the Millennium +5 Summit - Tilman Brück; Kevin Watkins (Weekly Report, 2005)
Extreme poverty blights the lives of one fifth of the world's population and denies more than 100 million children per year the chance of an education. Today in sub-Saharan Africa alone 45 million children are out of school and 313 million people are living on less than US 1 a day. 2005 provides an opportunity for rich countries to help put in place effective and cost-efficient strategies needed to change this picture in the long run. The world can choose to continue on its current course, leading to increased poverty and additional human suffering, or to adopt an agenda in favour of expanded human welfare and human security. This agenda is incorporated in the Millennium Development Goals still achievable with an increased support from Germany and the EU. However, in order for this to happen, the heads of state and government at the G8 Summit in Gleneagles and at the Millennium+5 Summit in New York this summer must make the right political decisions. We propose an analysis that can serve as the basis for discussions and decisions during these summits. Germany has then potential to assume an internationally significant role in the key areas of human development, trade policy and human security and thus credibly promote further reforms to alleviate poverty within the G8 states, the European Union and the United Nations.
Keywords: 330